Investigation of highly efficient particulate air filter media performance in existence of internal leak - Abraham, Daniel M. (My University, 2025)
High-efficiency particulate air (HEPA) and ultra-low particulate air (ULPA) filters are extensively utilized in nuclear and National Bio and Agro-Defense facilities as the last line of defense for eliminating particles from a contaminated gas stream prior to its release into the surrounding environment. The objective of the present study is to develop a computational tool capable of simulating the microstructure of such a filter medium. This tool will provide valuable information for enhancing the design and manufacturing of the scanning device used in the leak penetration test. It will also help in investigating the testing criteria set in the standards for classifying filter types. Consequently, it will assist in assessing the likelihood of a successful filtration leak test, thereby reducing the risk of an inaccurate test. The initial phase of this study was the design and construction of a biofiltration testing rig that adheres to the standards set by the American Society of Heating, Refrigerating and Air Conditioning Engineers (ASHRAE) 52.2 for HEPA testing. The purpose of this rig is to assess various prototypes of biocontainment housings used in the National Bio and Agro-Defense Facility (NBAF), along with their corresponding auto scan technologies against the traditional penetration test method. We evaluated the local and overall filter efficiency of two of the available housing units using their associated auto scanning methodologies, and we compared the results with the efficiency obtained using the conventional penetration test approach described in ASHRAE 52.2. A series of prerequisite tests were carried out to verify aerosol distribution uniformity upstream and downstream as well as the consistency of the injection and sampling probe measurements. This allowed us to investigate the impact of the filter pinholes (leaks) on the pressure drop and efficiency of the filter and enhanced our understanding of the protocols and requirements for comprehensive testing of large-scale pleated 610×610×292 mm³ HEPA and other filters at different flow rates. In the second part of the study, following an understanding of the scanning technology used to test the filter in the first part, we developed a three-dimensional fibrous computational model featuring non-homogenous fibers that replicates the HEPA filter sheet. This model was utilized to simulate and analyze the pressure drop and collection efficiency of the HEPA filter sheet, considering scenarios both with and without leaks. We expanded our work by building a small-scale filter sheet testing rig to compare experimental and computational results and determine a correlation between HEPA intact and leaky filter efficiencies. Our research revealed the optimal most penetrating particle size (MPPS) at which to test a filter and the minimum leak size at which the filter efficiency becomes independent of particle size and filtration velocity, which can be used to derive a designated leak penetration value for a successful leak penetration test under particular sampling and scanning conditions.
Keywords: High-efficiency particulate air filter; National Bio and Agro-Defense Facility; Scan leak test; Designated leak penetration; Fiber model; Filtration efficiency